The Effect Of Tax Extensification On Rural And Urban Land And Building Tax Revenue (PBB P2) On The Regional Income Management Agency (Bappenda) Sumedang Regency - Ani Sopiyani; Fahrul Alam Masruri; Apiatno (LPPM Universitas Sebelas April, 2021)
This research aims to know how to much the influence of tax extensification has on land and building tax revenues at the Regional Revenue Management Agency of Sumedang Regency. The method used in the preparation of this thesis is a descriptive quantitative method with a survey approach. The sample taken in this study used a saturated sampling method which was conducted on 20 respondents from the data collection and assessment section of the Tax Office of the Regional Revenue Management Agency of Sumedang Regency. The data collection techniques used were field research, questionnaires, observation and literature study. The testing technique used is validity test, reliability test, normality test, simple regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study indicate that the tax extensification in Sumedang Regency is very good with a total score of 861 or 86,1% Land and building tax revenue in Sumedang Regency is very good with a total score of 896 or 89,6%. The effect of tax extensification on rural and urban land and building tax revenues in Sumedang Regency is 27.9% and there are still 72.1% other factors. The results of the hypothesis test turned tcount > ttable or 2,637 > 1.7406. From these results it can be said that there is a significant effect between tax extensification on land and building tax revenues in rural and urban areas.